Yes-Associated Protein in Atherosclerosis and Related Complications: A Potential Therapeutic Target That Requires Further Exploration - Sun, Congrui; He, Bin; Sun, Mingsheng; Lv, Xiaoshuo; Wang, Feng; Chen, Jie; Zhang, Jianbin; Ye, Zhidong; Wen, Jianyan; Liu, Peng (Frontiers in Cardiovascular Medicine, 2021)
Atherosclerosis and its complicating diseases remain a leading cause of cardiovascular morbidity and mortality, bringing a massive burden on public health worldwide. Recognized as a chronic inflammation process, the initiation and development of atherosclerosis involve several highly correlated processes, including lipid metabolism disorder, endothelial cell dysfunction, inflammation, oxidative stress, vascular smooth cell activation, platelet activation, thrombosis, altered matrix metabolism, and vascular remodeling. Within the past few decades, there has been accumulating evidence proving the Yes-associated protein (YAP), the major effector of the Hippo pathway, can play a crucial role in the pathogenesis and development of atherosclerosis. The activation of YAP relating pathways, induced by multiple stimulations such as alerting flow pattern and matrix stiffness, can regulate processes including vascular endothelial cell dysfunction, monocyte infiltration, and smooth muscle cell migration which contribute to atherosclerotic lesion formation. Furthermore, YAP has been revealed by recent studies to potentially modulate atherosclerotic complications such as vascular calcification and intraplaque hemorrhage, which need further investigation. Thus, we summarized the relevant literature to outline current findings of the role that YAP plays in atherosclerosis and pave the way for future research.